Clergy Education and the Development of Emotional Intelligence: An Analysis of United Methodist Clergy in Kentucky: - White, Douglas A. (Christian education journal, 2019)
Research on the emotional intelligence of United Methodist clergy in the Kentucky Annual Conference is being conducted utilizing the Emotional Quotient 2.0 (EQ-i 2.0) assessment. Over 20% of active clergy have been assessed thus far and several trends are becoming evident. Specifically, of interest are those clergy persons who have engaged in graduate-level theological education and those who have not. This research seeks to add to the scholarly dialogue on understanding the impact of theological education in the formation of clergy leadership.